The information society : - Feather, John (Facet, 2008)
The book explores the information revolution that continues to gather pace. The commercial value of information becomes increasingly important in a world where data can be transmitted in a split second. This latest edition takes full account of significant developments since 2004. The advanced technologies and systems of a decade ago are falling into disuse; the floppy disk has all but vanished, and the CD-ROM will surely follow.Simple phrases like 'Web 2.0' or 'the social web' conceal rather than explain the significance of the concepts that they embody. As the quantity of personal digitized information continues to grow exponentially, so do both the benefits of exploiting it and the dangers of misusing it. The use of ICT to make government more accessible has to be balanced against the use of technologies that enable the state to be more vigilant or more intrusive, according to one's point of view. Behind all of this lies further technical change: the massive expansion of connectivity to high-speed broadband networks; the phased abandonment of analogue broadcasting; and the development of multi-functional mobile devices which carry voice, video and data and which can themselves be carried anywhere.The implications for daily life, for education, for work and for social and political relationships are massive. This questioning, open-minded look at the information profession and its break-out from the traditional boundaries of librarianship will interest all information professionals. It is also invaluable for students on courses in information, librarianship and communications studies, where an understanding of the nature of the information society is an essential underpinning of more advanced work